Hydrogen-rich syngas production via steam reforming of Palm Oil Mill Effluent (POME) – A thermodynamics analysis - Cheng, Y. W.; Cheng, C. K. (2018)
According to the oil world’s statistical data [1], the world production of edible vegetable oils was approximately 190 million tons in 2014/2015, which constituent of 32.71% of palm oil. The oil palm industry in Southeast Asia enjoyed prospering development, notably in the top three palm oil producing countries (Indonesia, Malaysia, and Thailand). In spite of this, the palm oil processing always associated with the concomitant production of several biomass wastes, namely palm oil fuel ash (POFA), palm oil mill effluent (POME), palm kernel shells (PKS), empty fruit bunches (EFB), and oil palm frond (OPF) [2, 3]. Among the biomass wastes, the POME wastewater itself is the most haunting pollutant because of its enormous quantity (2.5 – 3.75 tons of POME produced/ton crude palm oil processed) and highly polluted characteristics (COD: 15,000 – 100,000 ppm and BOD: 10,250 – 43,750 ppm) [4, 5]. In Malaysia alone, the crude palm oil production in 2017 was 19,919,331 tons [6], therefore circa 49.80 – 74.70 million tons of POME was generated. It is envisaged that this vast quantity of POME could be ameliorated into a significant amount of syngas (H2 and CO) via its steam reforming, whereby this continuous supply of biomass-derived hydrogen energy able to support future local electricity generation.